(untitled) (Olhar de Professor, 2021)
In this article we seek to discuss the proposals for special education in the context of the COVID-19 pandemic. Based on the theoretical and methodological assumptions of historical and dialectical materialism, we analyze international and national documents that propose non-classroom teaching alternatives for special education students. We verified the participation of multilateral organizations in the diffusion of new ways of producing education in the world and in building the consensus that, in Brazil, remote education is the only way to adjust the school calendar in this context. We found that the recommendations for the education of special education students do not differ from the proposals for face-to-face teaching already disseminated by educational policies, although they recognize that these students do not benefit from distance solutions. We conclude that the proposals for special education in the period of the pandemic exposed the exclusion of access to scientific knowledge, which historically permeates the education of these groups of students.